Dietary Intake and Nutritional Status of Children in Kajang: A Study at An Indigenous Area in Indonesia - Fatmawaty Mallapiang; Andi Syamsiah Adha; Rini Jusriani; Masyitha Muis (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Malnutrition in children can contribute to growth limitations, and susceptibility to infection, which ultimately can inhibit the children’s growth and development. This study aimed to determine the fulfillment of macronutrient intake, micronutrient intake, and nutritional status of elementary school children at State Elementary School (hereafter SDN) Ammatoa Area, Kajang District, and Bulukumba Regency. This research was a descriptive study involving a population of 131 children and a sample of 65 children obtained by accidental sampling. The data were analyzed by using descriptive analysis of the percentage test. The results showed that the majority of macro-carbohydrate intakes (56.9%) were in the sufficient category, the majority of protein and fat (61.5% and 84.6%) were in the less category, while the intake of micronutrients, namely iron, zinc, and calcium primarily (83.1%, 80%, and 92.3%) in the less category, and the majority of nutritional status (86.2%) in the normal category. It was concluded that the intake of macro and micronutrients in elementary school children at the SDN Ammatoa region tended to be still lacking/low, despite their nutritional status, which tended to be normal. It is hoped that the relevant agencies will provide counselling to students regarding healthy and nutritious food by utilizing local food diversification in the Ammatoa customary area.